Changes in sphingomyelins and ceramides with very long-chain polyunsaturated fatty acids during spermatogenic cell differentiation - Oresti, Gerardo Martin (2010)
In seminiferous tubules, Sertoli cells and spermatogenic cells at different stages of differentiation coexist. In this study, pachytene spermatocytes and round spermatids were isolated from rat seminiferous tubules to study how ceramides (Cer) and sphingomyelins (SM) with very long chain polyunsaturated fatty acids (VLCPUFA) change during spermatogenesis. Although the concentration of phospholipids including SM was similar in both cell types, there were many differences in their fatty acids (FA). SM and Cer had 28:4n-6, 30:5n6 and 32:5n-6 as their main FA in spermatocytes, but both lipids contained mostly 28:4n-6 in spermatids. In turn, spermatids, but not spermatocytes, contained an important proportion of 2-hydroxylated versions of the mentioned VLCPUFA (2-OH VLCPUFA). The 2-OH VLCPUFA / non-hydroxy VLCPUFA ratio not only increased markedly in SM and Cer with germ cell differentiation but was even higher in (epididymal) spermatozoa. Although the enzyme that is responsible for the synthesis of the 2-OH VLCPUFA of SM and Cer remains to be investigated, our results suggest that it is expressed after completion of meiosis. Residual bodies, which contain materials -including lipids- that are discarded from late spermatids (elongatingcondensing forms) as they differentiate to spermatozoa, were unusual in that they contained no Cer but plenty of SM with almost exclusively 2-OH VLCPUFA. Taking into account that residual bodies are normally phagocytosed by Sertoli cells, the eventual fate of these SM species is another intriguing question to be solved regarding sphingolipid metabolism during the spermatogenic cycle